If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(y) = ln(x) + ln(x + 13) + ln(C) Multiply ln * y lny = ln(x) + ln(x + 13) + ln(C) Multiply ln * x lny = lnx + ln(x + 13) + ln(C) Reorder the terms: lny = lnx + ln(13 + x) + ln(C) lny = lnx + (13 * ln + x * ln) + ln(C) lny = lnx + (13ln + lnx) + ln(C) Multiply ln * C lny = lnx + 13ln + lnx + lnC Reorder the terms: lny = 13ln + lnC + lnx + lnx Combine like terms: lnx + lnx = 2lnx lny = 13ln + lnC + 2lnx Solving lny = 13ln + lnC + 2lnx Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-13ln' to each side of the equation. -13ln + lny = 13ln + lnC + -13ln + 2lnx Reorder the terms: -13ln + lny = 13ln + -13ln + lnC + 2lnx Combine like terms: 13ln + -13ln = 0 -13ln + lny = 0 + lnC + 2lnx -13ln + lny = lnC + 2lnx Add '-1lnC' to each side of the equation. -13ln + -1lnC + lny = lnC + -1lnC + 2lnx Combine like terms: lnC + -1lnC = 0 -13ln + -1lnC + lny = 0 + 2lnx -13ln + -1lnC + lny = 2lnx Add '-2lnx' to each side of the equation. -13ln + -1lnC + -2lnx + lny = 2lnx + -2lnx Combine like terms: 2lnx + -2lnx = 0 -13ln + -1lnC + -2lnx + lny = 0 Factor out the Greatest Common Factor (GCF), 'ln'. ln(-13 + -1C + -2x + y) = 0Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-13 + -1C + -2x + y)' equal to zero and attempt to solve: Simplifying -13 + -1C + -2x + y = 0 Solving -13 + -1C + -2x + y = 0 Move all terms containing l to the left, all other terms to the right. Add '13' to each side of the equation. -13 + -1C + -2x + 13 + y = 0 + 13 Reorder the terms: -13 + 13 + -1C + -2x + y = 0 + 13 Combine like terms: -13 + 13 = 0 0 + -1C + -2x + y = 0 + 13 -1C + -2x + y = 0 + 13 Combine like terms: 0 + 13 = 13 -1C + -2x + y = 13 Add 'C' to each side of the equation. -1C + -2x + C + y = 13 + C Reorder the terms: -1C + C + -2x + y = 13 + C Combine like terms: -1C + C = 0 0 + -2x + y = 13 + C -2x + y = 13 + C Add '2x' to each side of the equation. -2x + 2x + y = 13 + C + 2x Combine like terms: -2x + 2x = 0 0 + y = 13 + C + 2x y = 13 + C + 2x Add '-1y' to each side of the equation. y + -1y = 13 + C + 2x + -1y Combine like terms: y + -1y = 0 0 = 13 + C + 2x + -1y Simplifying 0 = 13 + C + 2x + -1y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 0.5x+x=172 | | Tanydx=-xdy | | -4+5+-3= | | 8v-26=3(v+5) | | -8/v-2=5 | | 0.5x+x=165 | | 2x-1+2x-9+x=180 | | 1=0.5x-0.6x-7 | | 71+25+x=180 | | 93+50+x=180 | | 96+45+x=180 | | 104+29+x=180 | | 105+23+x=180 | | -73+2y+6=2(4y-2)9 | | 3x+2=-2x-2 | | (f+6)squared=144 | | 42=3v+12 | | 3(x^2-2x-8)=0 | | 6x-2y=-30 | | 5+x=2x-3-8 | | 3(x-6)=6(x-3) | | 360=x+(9x-35)+(x-46)+.5x | | 2x-19=(-5)x+9 | | 2u-11=5(u+2) | | x-7=4x+1 | | 8x+18=3x+-7 | | 6x+1=4x-13 | | (x-15)-(2x-13)=1 | | 6x(6x)+5(3x(3x)-x)-3x= | | 4x-3+90=180 | | f(x)=500-75x | | 3x(x-2)=24 |